Reducing thermal stress and improving efficiency in HCPV cells using CFD-optimized pin-finned microchannel cooling - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
High-concentration photovoltaic (HCPV) systems can achieve high electrical efficiencies, but their performance is constrained by the intense and spatially non-uniform thermal loads generated under high solar concentration. This work presents a three-dimensional conjugate heat-transfer analysis of microchannel cooling strategies for HCPV cells operating at CR = 1000, evaluating (i) pin-fin geometry, (ii) pin rotation, and (iii) differential flow distribution, together with Newtonian water and a shear-thinning nanofluid. The full multilayer GaInP/GaInAs/Ge assembly is explicitly resolved using fine-resolution finite-volume simulations, and the thermal model is validated against published experimental data. Pin-fin microchannels reduce maximum temperature difference by up to 11.9% and average temperatures by up to 9.68% relative to smooth channels. Differential flow allocation further decreases non-uniformity by up to 5.21%, while nanofluid rheology lowers peak-temperature differences by an additional 2%-3% at high flow rates. These improvements increase net electrical output to 37.75 W for the best-performing configuration. The resulting reduction in temperature gradients also decreases thermoelastic stress within the multilayer structure, with the optimized configuration lowering the maximum stress by up to 19.4%. An environmental assessment-based on representative operating conditions and carbon-pricing parameters-indicates annual CO2 reductions of up to 1.55% per m2 and carbon-cost savings on the order of 4.5 x 104 USD/(year m2). The results show that geometry-tailored microchannels combined with shear-dependent coolant rheology can reduce peak temperatures, temperature gradients, and associated stress levels in high-flux photovoltaic receivers.